Spatiotemporal control of translation in live zebrafish embryos via photoprotected mRNAs - Florian P. Weissenboeck; Melissa Pieper; Helena Schepers; Sophie Hötte; Nils Klöcker; Sabine Hüwel; Andreas van Impel; Stefan Schulte-Merker; Andrea Rentmeister (Communications Chemistry)
Abstract Translation of mRNA into protein is a fundamental process and tightly controlled during development. Several mechanisms acting on the mRNA level regulate when and where an mRNA is expressed. To explore the effects of conditional and transient gene expression in a developing organism, it is vital to experimentally enable abrogation and restoration of translation. We recently developed the FlashCaps technology allowing preparation of translationally muted mRNAs and their controlled activation by light. Here, we validate its functionality in vivo. We demonstrate that translation of FlashCap-eGFP-mRNA can be triggered in zebrafish embryos with spatiotemporal control. The injected FlashCap-mRNA is stable for hours and remains muted. Light-mediated activation up to 24 h post fertilization produces visible amounts of eGFP and can be restricted to distinct parts of the embryo. This methodology extends the toolbox for vertebrate models by enabling researchers to locally activate mRNA translation at different timepoints during development.